1986
DOI: 10.1177/153857448602000503
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoplastic Aorto-Iliac Syndrome: A Critical Approach to Its Pathogenesis

Abstract: The clinical and angiographic features of 12 patients showing a significant reduction in the diameters of the distal aorta and the common iliac arteries are described. All the patients were women aged between 23 and 63 years (average age: 49 years), heavy smokers in the majority. An associated aortic arch syndrome was observed in 5 patients. Type IV dyslipidemia was found in 5. In 10 patients the erythrocyte sedimentation rate was increased. Claudication of the lower limbs, without dystrophic phenomena, was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This fact indicates a possible role of infl ammatory diseases, such as Takayasu's aortoarteritis. 6 The importance of the technical aspects of reconstructive surgery in patients with HAIS has been emphasized. Burke et al showed ePTFE grafts to have a superior patency rate in comparison to Dacron.…”
Section: Discussionmentioning
confidence: 99%
“…This fact indicates a possible role of infl ammatory diseases, such as Takayasu's aortoarteritis. 6 The importance of the technical aspects of reconstructive surgery in patients with HAIS has been emphasized. Burke et al showed ePTFE grafts to have a superior patency rate in comparison to Dacron.…”
Section: Discussionmentioning
confidence: 99%